The Influence of Parental Socioeconomic Status and Educational Attainment on Students’ Motivation to Pursue Upper Secondary Education - Bridget Uwameiye; Oladitan Sam Tunde; Nyamonge Kenya; Sopho Midelashvili; Svitlana Syn'ohub (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze the influence of parental socioeconomic status and parental education level on students' motivation to continue their education to senior high school level in Lagos, Nigeria, both partially and simultaneously, in order to understand family factors that influence students' educational sustainability. Methodology: This study employed a quantitative approach with a descriptive-correlational design. The sampling technique used simple random sampling of 36 parents in Lagos, Nigeria. Data collection was conducted through questionnaires, observations, structured interviews, and documentation. Data analysis used multiple linear regression with the assistance of IBM SPSS Statistics 21 software, including tests for normality, linearity, multicollinearity, heterogeneity, and autocorrelation. Main Findings: The results of the study indicate that parental economic status and parental education level simultaneously significantly influence students' motivation to continue their education to high school. Parental education level has the most dominant influence compared to economic status. The coefficient of determination value of 0.994 indicates that both variables are able to explain 99.4% of the variation in students' motivation to continue their education. Novelty/Originality of this study: The novelty of this study lies in its integrated analysis of the influence of socioeconomic status and parental education level on students' motivation to pursue higher secondary education in an urban Nigerian context. This study provides new insights into the dominance of parental education over economic factors in shaping students' educational motivation.